A dialética do cuidado: cuidar de si e cuidar do outro no processo de envelhecimento de cuidadores não remunerados - Mendiondo, Micaela (Universidade Federal de São Carlos, 2026)
Population aging, resulting from declining birth rates and advances in health care and socioeconomic conditions, has intensified the demand for long-term care. In Brazil, this responsibility remains predominantly within the family sphere, with limited state support, which contributes to the invisibility and feminization of informal care work. Therefore, it is necessary to understand how caregivers make sense of care and self-care throughout the aging process. Objective: To analyze informal caregivers’ perceptions of caring for others and selfcare, considering their implications across different age groups and in their own aging process. Method: This is a qualitative study grounded in historical-dialectical materialism and Historical-Cultural Psychology. Nine informal caregivers of older adults participated and responded to semi-structured interviews. Thematic analysis was conducted, from which categories and subcategories emerged, as well as identified tensions. Results and Discussion: The resulting categories were Care, Self-care, Learning, Work, and Aging. Four central tensions were identified: individual versus collective; living versus surviving; formal work versus care work; and care guaranteed to others versus lack of protection in one’s own old age. Final Considerations: Care, although sustained by affective bonds, remains structured by inequalities that keep it within the private sphere. The findings reinforce the need for integrated public policies, such as the National Care Policy, that promote social co-responsibility and protection for caregivers throughout the life course, contributing to debates in Critical Gerontology and the Psychology of Aging.
The dialectic of care: caring for oneself and caring for others in the aging process of unpaid caregivers
Keywords: Envelhecimento; Cuidadores familiares informais; Cuidado; Autocuidado; Política Nacional de Cuidados; CIENCIAS SOCIAIS APLICADAS::DEMOGRAFIA::POLITICA PUBLICA E POPULACAO::POLITICAS DE PLANEJAMENTO FAMILIAR; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO TRABALHO E ORGANIZACIONAL; CIENCIAS HUMANAS::PSICOLOGIA; 3. Saúde e Bem-Estar; 5. Igualdade de Gênero; 8. Trabalho Decente e Crescimento Econômico; 10. Redução das Desigualdades; 11. Cidades e Comunidades Sustentáveis